2017
DOI: 10.1136/bmjopen-2017-017430
|View full text |Cite
|
Sign up to set email alerts
|

Associations between polypharmacy and treatment intensity for hypertension and diabetes: a cross-sectional study of nursing home patients in British Columbia, Canada

Abstract: ObjectivesDescribe nursing home polypharmacy prevalence in the context of prescribing for diabetes and hypertension and determine possible associations between lower surrogate markers for treated hypertension and diabetes (overtreatment) and polypharmacy.DesignCross-sectional study.Setting6 nursing homes in British Columbia, Canada.Participants214 patients residing in one of the selected facilities during data collection period.Primary and secondary outcome measuresPolypharmacy was defined as ≥9 regular medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 21 publications
1
33
1
1
Order By: Relevance
“…In similar studies conducted among diabetes patients in Brazil and Saudi Arabia, it was 57% and 78%, respectively [16,18]. 48% of patients with diabetes and hypertension in Canada were prescribed �9 medicines [19]. The average number of medicines prescribed to T2DM patients in India and Germany was five and 12, respectively [15,20].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In similar studies conducted among diabetes patients in Brazil and Saudi Arabia, it was 57% and 78%, respectively [16,18]. 48% of patients with diabetes and hypertension in Canada were prescribed �9 medicines [19]. The average number of medicines prescribed to T2DM patients in India and Germany was five and 12, respectively [15,20].…”
Section: Discussionmentioning
confidence: 83%
“…In patients, it can adversely affect their adherence to medicines, quality of life and life expectancy, can lead to suboptimal blood glucose control and hospital admissions, and can increase severe hypoglycaemia risk and healthcare costs [10][11][12][13][14]. Studies conducted in different diabetes (including T2DM) populations and settings have reported a range of polypharmacy prevalence figures (6-85%) [15][16][17][18][19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 214 elderly people in Canada also found an association between polypharmacy and more intensive pharmacological treatments to treat hypertension and diabetes. However, in this study, the sample consisted of very fragile and institutionalized elderly people (17) .…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of polypharmacy also varies between the elderly living in the community and the elderly living in the nursing home. Among the patients living in the community, the incidence rates of 41%, 43.4%, 35.8% and 46.8% were reported from Iceland, USA, Australia and Italy, respectively (10)(11)(12). In a recent study conducted among nursing homes as a report of shelter work in eight European countries, the incidence rate was reported to be 49.7% (13).…”
Section: Discussionmentioning
confidence: 99%